Genome‐wide association study for frost tolerance in rapeseed/canola (Brassica napus) under simulating freezing conditions. (4th November 2019) - Wrucke, Danielle F.; Talukder, Zahirul I.; Rahman, Mukhlesur
Abstract: Rapeseed/canola seedlings can be easily damaged by spring frost, which can rupture the cells and kill the plant. Genetic variations for frost tolerance have known to exist within rapeseed/canola gene pool. A genome‐wide association study (GWAS) was conducted using 231 diverged rapeseed/canola germplasm to find the significant markers of the freezing tolerance traits. The genotypes were obtained from 21 countries and comprised of spring, winter and semi‐winter growth types. The genotypes were evaluated in plant growth chamber under simulated freezing conditions. Highly significant genotypic variation was observed for the freezing tolerance. The best three freezing tolerant germplasms (Rubin, KSU‐10, and AR91004) were winter type, while the four most freezing susceptible germplasms (Polo Canada, Prota, Drakkar, and BO‐63) were all spring type. No geographical or growth habit type clusters were identified by structure analysis in this mixed population. One QTL was identified that was located on chromosome A02. Six freezing/abiotic stress tolerance genes have been identified in this study.